Peningkatan Keterampilan Menulis Mata Pelajaran Bahasa Indonesia Melalui Penggunaan Media Gambar Berseri Pada Siswa Kelas V di MI Darul Ulum 01 Kudus - Bibit bit Muzdalifah; Naila Alfa Khusna; Eva Luthfi Fakhru Ahsani (Latifah Pres, 2022)
The four skills students must have to learn Indonesian are listening, speaking, reading, and writing. However, in its application when studying Indonesian there are some students who have weak writing skills. Based on initial observations in teaching and learning activities, Indonesian does not attract attention and interest in learning, students are less skilled in writing skills. The purpose of this study was to find out the improvement of writing skills in the Indonesian subject through the use of serial picture media for fifth grade students at MI Darul Ulum 01 Kudus. This research method is Classroom Action Research (CAR). The subjects of this study were students of class V Mi Darul Ulum 01 Kudus with a total of 28 students. This research was conducted in two cycles. The results of the study show that the use of serial image media can improve short essay writing skills. This can be proven by the acquisition of student activity scores which increased from cycle I 69.60% to 84.24% in cycle II. It can be concluded that research using serial image media has increased. Keywords: Serial picture media, Short essay writing skill, student activity